2017
DOI: 10.4314/ejhs.v27i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter Pylori with Presence of Myocardial Infarction in Iran: A Systematic Review and Meta-Analysis

Abstract: BackgroundOver the past decade, cardiovascular diseases have been recognized as the leading cause of mortality worldwide. Myocardial infarction (MI) is one of the most prevalent types of cardiovascular diseases that is caused by the closure of coronary arteries and ischemic heart muscle. Numerous studies have analyzed the role of H. pylori as a possible risk factor for coronary artery diseases, in most of which the role of infection in coronary artery disease is not statistically significant.MethodsThese contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Several studies have been published on H. pylori and cardiovascular disease; the most recent meta-analyses in 2017 by Yu et al [41] reported a significant association with coronary artery disease, and by Rahmani et al [42] with myocardial infarction. It has been hypothesized that H. pylori may facilitate atherosclerosis by promoting chronic inflammation, dyslipidemia and endothelial dysfunction [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published on H. pylori and cardiovascular disease; the most recent meta-analyses in 2017 by Yu et al [41] reported a significant association with coronary artery disease, and by Rahmani et al [42] with myocardial infarction. It has been hypothesized that H. pylori may facilitate atherosclerosis by promoting chronic inflammation, dyslipidemia and endothelial dysfunction [41].…”
Section: Discussionmentioning
confidence: 99%
“…To it, H. pylori ‐positive geriatric patients have increased risk of developing atherosclerosis and acute coronary syndrome (Carvalho et al, ; Lai, Yang, Lin, & Kao, ). They are also at the risk of acquiring myocardial infraction, stroke, and peripheral artery disease (Rahmani et al, ; Vijayvergiya & Vadivelu, ).…”
Section: Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…However, H. pylori was not isolated from any atherosclerotic plaques in the studies in Italy and Poland [97][98]. Rahmani et al demonstrated in their meta-analysis study that there was a signi cant relationship between the infection with H. pylori and Myocardial infraction in the Iranian patients (ORs = 2.53) [99]. In a meta-analysis of 18 epidemiological studies Danesh et al found no signi cant relationship between H. pylori infection and the coronary heart disease (CHD) [100].…”
Section: Discussionmentioning
confidence: 99%